Magnesium Technology 2017 - Solanki, Kiran N.; Orlov, Dmytro; Singh, Alok.; Neelameggham, Neale R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The Magnesium Technology Symposium, the event on which this collection is based, is one of the largest yearly gatherings of magnesium specialists in the world. Papers represent all aspects of the field, ranging from primary production to applications to recycling. Moreover, papers explore everything from basic research findings to industrialization. Magnesium Technology 2017 covers a broad spectrum of current topics, including alloys and their properties; cast products and processing; wrought products and processing; forming, joining, and machining; corrosion and surface finishing; ecology; and structural applications. In addition, there is coverage of new and emerging applications.
of deformation behavior of wrought Mg alloys -- Effect of Thermo-mechanical Treatment of Extruded Z1 Mg Alloy on Resulting Mechanical Properties -- In-situ investigation of deformation mechanisms in Mg-Zn-Y magnesium alloy with LPSO phase by diffraction methods and acoustic emission -- Part 13: In-situ Methods for Unraveling Structure-Property Relationships in Light Metals: Diffraction and Other Novel Methods -- Structural evolution of metals at high temperature: Complementary investigations with neutron and synchrotron quantum beams -- Advanced Aluminum Alloys Development and In-Situ Fitness-for-Service Testing in Automotive Lightweighting -- In-situ X-ray Synchrotron Profile Analysis during High Pressure Torsion of Ti -- The Effect of Grain Refinement on Hot Tearing in AZ91D Magnesium Alloys -- Formability of Magnesium Alloy AZ31B from Room Temperature to 125C under Biaxial Tension -- In-situ real-time monitoring of aging processes in an aluminum alloy by high-precision dilatometry -- Effect of the Zn content on the compression behaviour of Mg5Nd(Zn): an in situ synchrotron radiation diffraction study.
Keywords: Metals; Materials -- Analysis; Materials; Metals and Alloys; Characterization and Analytical Technique; Materials Engineering